2020
DOI: 10.1001/jamaneurol.2019.2861
|View full text |Cite
|
Sign up to set email alerts
|

Association of Cavum Septum Pellucidum and Cavum Vergae With Cognition, Mood, and Brain Volumes in Professional Fighters

Abstract: IMPORTANCE Many studies have investigated the imaging findings showing sequelae of repetitive head trauma, with mixed results.OBJECTIVE To determine whether fighters (boxers and mixed martial arts fighters) with cavum septum pellucidum (CSP) and cavum vergae (CV) have reduced volumes in various brain structures or worse clinical outcomes on cognitive and mood testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…39 However, studies have suggested that their presence is associated with cognitive dysfunction in patients with prior head trauma. 61 Also, the size and frequency of cavum septi pellucidi and cavum vergae were greater in patients with schizophrenia, alcoholism, and prior head trauma. 62 The cavum septi pellucidi is a normal finding in fetuses between 18 and 37 weeks of gestation, and its absence is associated with multiple significant CNS abnormalities.…”
Section: Cavum Septi Pellucidi Cavum Vergae and Cavum Veli Interpositimentioning
confidence: 90%
“…39 However, studies have suggested that their presence is associated with cognitive dysfunction in patients with prior head trauma. 61 Also, the size and frequency of cavum septi pellucidi and cavum vergae were greater in patients with schizophrenia, alcoholism, and prior head trauma. 62 The cavum septi pellucidi is a normal finding in fetuses between 18 and 37 weeks of gestation, and its absence is associated with multiple significant CNS abnormalities.…”
Section: Cavum Septi Pellucidi Cavum Vergae and Cavum Veli Interpositimentioning
confidence: 90%
“…Subcortically, lower thalamic volumes have been associated with earlier age of initiating American football participation among retired professionals [ 48 ]. The Professional Fighters Brain Health Study investigated 476 active and former professional fighters (boxers and mixed martial artists; 92% active fighters and otherwise healthy) compared to 63 unexposed controls and found lower thalamus and corpus callosum volumes among fighters [ 49 ].…”
Section: Structural Mrimentioning
confidence: 99%
“…An enlarged CSP has been reported in contemporary neuroimaging (MRI) studies of boxers ( 25 ), active and retired mixed martial arts fighters ( 26 ), and retired professional football players ( 27 29 ). Additionally, Wilde et al identified expansion of the frontal horns of the lateral ventricles in a mixed cohort of active and retired boxers using the Evans' index (i.e., the ratio of the maximal transverse diameter of the frontal horns of the lateral ventricles to the maximal internal diameter of the cranium).…”
Section: Introductionmentioning
confidence: 90%